SPPS Resins Impact the PNA-Syntheses' Improvement - Pipkorn, Rüdiger (Ivyspring International Publisher, 2013)
The personalized medicine, also documented as “individualized medicine”, is an effective and therapeutic approach. It is designed to treat the disease of the individual patient whose precise differential gene expression profile is well known. The trend in the biomedical and biophysical research shows important consequences for the pharmaceutical drug and diagnostics research. It requires a high variability in the design and safety of target-specific pharmacologically active molecules and diagnostic components for imaging of metabolic processes. A key technology which may fulfill the highest demands during synthesis of these individual drugs and diagnostics is the solid phase synthesis which is congenial to automated manufacturing. Additionally the choice of tools like resins and reagents is pivotal to synthesize drugs and diagnostics in high quality and yields. Here we demonstrate the solid phase synthesis effects dependent on the choice of resin and of the deprotection agent.